+0  
 
0
180
1
avatar

14-[(-4)-(-6)]+(7-9)

Guest Sep 13, 2017
 #1
avatar+314 
0

First, let's solve whats in the brackets.

-4-(-6)

=-4+6

=2

 

Now let's do the other bracket.

7-9=-2

 

Finally, plug those two numbers into the expression.

14-2+(-2)

=14-2-2

=10

 

angel

ISmellGood  Sep 13, 2017

10 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.